Aesthetic discourse in the significance of commercial advertisement designs (Al-Academy, 2023)
The current research is concerned with the study of (aesthetic discourse in the significance of commercial advertisement designs), according to a knowledge structure defined by function and creativity, and the main goal is to interpret the reality of forms, their various sources, their essence, meanings, formal relationships, and design ideas in order to achieve the visual goal as a typographic achievement. It arises through the designer’s internal mental intuition to produce shapes based on subjective feelings that refer his preconceptions about those shapes with his feelings to creative formations. Aesthetic discourse is produced from the mind depending on the various symbolic, psychological and social functions, production methods, customs and traditions, so the aesthetic discourse is a reflection of this social and economic reality. .This study is a sign capable of enriching the aesthetic discourse with many data that stimulates the sense of taste in the recipient through its specificity in the multiplicity of symbols and connotations and its absorption of its effective importance that brings together the designer as a creator of the aesthetic discourse and the society that preserves in his memory many rhetorical and aesthetic patterns, and no matter how many theories of discourse The discourse is associated with the function and the creative content, just as the language of the discourse is associated with the visual language to analyze the aesthetic discourse in it into a visual culture and to the processes of understanding, interpretation and persuasion.Where he dealt with the aesthetic discourse as an indicator that leads the designer towards creating constructive and aesthetic relationships to reach a specific goal that is compatible with the aspirations of the recipient through the designer’s tool in directing and employing these relationships and foundations within a visual unit that lies in the form that melts into the content with the rest of its constituent elements